Pembuatan Media Pertumbuhan Alternatif Pada Mikroorganisme Dengan Menggunakan Umbi Porang (Amorphophallus oncophyllus Prain) TERHADAP Staphylococcus aureus, Escherichia coli DAN Candida albicans - Marpaung, Jon Kenedy; Purba, Sondang; Juniwati Barus, Darwita; Iqlima, Dara (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
Porang tuber (Amorphophallus oncophyllus Prain) contains carbohydrates, fats, proteins, minerals, vitamins, and dietary fiber which are thought to be alternative growth media. This study aims to determine the growth of alternative media for microorganisms with Porang tubers. This research was conducted in the Pharmaceutical Chemistry laboratory, at Sari Mutiara University, Indonesia. Samples of Porang tubers were obtained from Porang plantations in the Amplas area, North Sumatra. This study uses an experimental method. Characterization of Porang tuber powder was found 9.54% water content, 9.09% water soluble extract content, and 1.43 total ash content.to contain%Secondary metabolites contained in Porang tuber starch were alkaloids and carbohydrates. The process of making starch begins with soaking with NaCl to remove the sap on the Porang tubers. Furthermore, the grating process is carried out until a precipitate of Porang tuber starch is found which will then be dried into Porang tuber starch. The manufacture of starch media respectively used a concentration of 5% (F1); 7.5% (F2) and 10% (F3). Then added agar, NaCl, and milk. Furthermore, microbiological tests were carried out using Staphylococcus aureus, Escherichia coli, and Candida albicans with the pour method. The comparison used is Nutrient agar and Potato dextrose agar. Furthermore, observations of the growth of these microorganisms were carried out. The results of the test Porang tuber starch showed yeast and bacteria growth media. The result of colony growth was found that the most colonies were found in formula 3 with Candida albicans as many as 297 colonies. The number of Staphylococcus aureus was found to be in formula 2 with 251 colonies, and for Escherichia coli, the most colonies were found in formula 3 with 143 colonies. Conclusion From the results of the study, it was found that Porang tubers can be used as growth media, Staphylococcus aureus, Escherichia coli, and Candida albicans.